2020
DOI: 10.3386/w27401
|View full text |Cite
|
Sign up to set email alerts
|

The Political Scar of Epidemics

Abstract: for helpful comments. We are also grateful to Kimiya Akhyani for providing very useful research assistance. Views presented are those of the authors and not necessarily those of the EBRD. All interpretations, errors, and omissions are our own. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 15 publications
0
26
0
1
Order By: Relevance
“…On the global level, the low student satisfaction with governments (not in line with the findings of Pan [30] and Baloran [47]) and banks shows that young generations do not trust them, although they were and are still providing some measures to alleviate the severe consequences of the COVID-19 pandemic [44]. In fact, according to Aksoy et al [115] the current epidemic could lead to the further erosion of satisfaction and trust in political leaders and institutions and may leave behind a long-lasting political scar on the current young generation. The selected socio-demographic factors influenced the level of satisfaction with institutions in the same way as was described by way of a general observation.…”
Section: Discussionmentioning
confidence: 96%
“…On the global level, the low student satisfaction with governments (not in line with the findings of Pan [30] and Baloran [47]) and banks shows that young generations do not trust them, although they were and are still providing some measures to alleviate the severe consequences of the COVID-19 pandemic [44]. In fact, according to Aksoy et al [115] the current epidemic could lead to the further erosion of satisfaction and trust in political leaders and institutions and may leave behind a long-lasting political scar on the current young generation. The selected socio-demographic factors influenced the level of satisfaction with institutions in the same way as was described by way of a general observation.…”
Section: Discussionmentioning
confidence: 96%
“…On a global level, a low students' satisfaction with governments (not in a line with findings of Pan [30] and Baloran [47] and banks reflects that young generations do not trust them although they were and are still providing some measures, dedicated to alleviate the severe consequences of the COVID-19 pandemic [44]. In fact, according to Aksoy et al [115] the current epidemic can result in the further erosion of satisfaction and trust in political leaders and institutions, and may leave behind a long-lasting political scar on the current young generation. The selected sociodemographic factors influenced the satisfaction with institutions in the same way as it was described as a general observation.…”
Section: Discussionmentioning
confidence: 96%
“…First, it is too early to tell whether the effects documented in this paper will be long lasting. Previous studies documented that the impact of job loss on attitudes toward welfare programs was short lived after the global financial crisis (Margalit 2013), whereas the impact of recessions (Giuliano and Spilimbergo 2014) and epidemics (Aksoy, Eichengreen, and Saka 2020) in forging attitudes of cohorts experiencing such upheavals during their "impressionable age" was found to be longer lasting. Even so, one might conjecture that the pandemic's acceleration after the survey's conclusion could have strengthened the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other factors may simultaneously be causing changes in attitudes. For example, other researchers have recently found that epidemics weaken trust in government (Aksoy, Eichengreen, and Saka 2020).…”
Section: Discussionmentioning
confidence: 99%